Posisi Semi Fowler terhadap Respiratory Rate untuk Menurunkan Sesak pada Pasien TB Paru - Suhatridjas Suhatridjas; Isnayati Isnayati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study was to determine the effect of the semi-fowler position on Respiratory Rate in pulmonary TB patients in the Pelni Hospital in Jakarta. The method used in this research is descriptive research with a case study approach. The results showed that there was a change in respiratory rate from 21x / min to 18x / min in the subject I and 22x / min to 19x / min in subject II for three days of treatment. In conclusion, there is a significant change in the patient's breathing ability before and after the intervention. Keywords: Semi Fowler Position, Respiratory Rate, Lung TB